2004
DOI: 10.4040/jkan.2004.34.7.1288
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Factors Influencing on Health Promoting Lifestyle in the Elderly: Application of Pender's Health Promotion Model

Abstract: The factors influencing on health promoting lifestyle for elderly were prior related behavior, perceived benefits of action, perceived self-efficacy, commitment to a plan of action, and interpersonal influences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 0 publications
2
23
0
3
Order By: Relevance
“…Social support was found to be a significant predictor of a HPL and the HRQOL. This result is similar to that of previous studies, in that 57% of them provided support for the importance of interpersonal influences as determinants of a HPL (Seo & Hah, 2004; Chen et al ., 2007; Thanakwang, 2008; Pender et al ., 2010). Other studies showed that social support significantly related to HRQOL (Ethgen et al ., 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Social support was found to be a significant predictor of a HPL and the HRQOL. This result is similar to that of previous studies, in that 57% of them provided support for the importance of interpersonal influences as determinants of a HPL (Seo & Hah, 2004; Chen et al ., 2007; Thanakwang, 2008; Pender et al ., 2010). Other studies showed that social support significantly related to HRQOL (Ethgen et al ., 2004).…”
Section: Discussionsupporting
confidence: 92%
“…The HPLP-II is a 52-item 4-point Likert scale based on Pender's health promotion model, which contains six subscales. Cronbach's ⍺ for this scale was .92, 17) and in this study, it was .91. Exercise self-efficacy was assessed using a modified version of Marcus et al 18) tool, revised and translated into Korean by three Korean nursing college professors.…”
Section: Measurementssupporting
confidence: 57%
“…Health-promoting behavior was assessed using a Korean version 17) of the Health-Promoting Lifestyle Profile II (HPLP-II). The HPLP-II is a 52-item 4-point Likert scale based on Pender's health promotion model, which contains six subscales.…”
Section: Measurementsmentioning
confidence: 99%
“…Algunos estudios realizados desde el modelo de Nola Pender 19,20 , también dan cuenta que los beneficios percibidos influyen en la adopción y compromiso de conductas promotoras de salud; por lo tanto se considera muy valioso el aporte que este modelo hace para la comprensión de las variables que pueden estar implicados en la adopción o no de conductas saludables, cuyo análisis puede ser útil para los profesionales de enfermería, en especial cuando se diseñan intervenciones encaminadas a mejorar el seguimiento y el cuidado temprano de las gestantes 21 . La principal fortaleza de este estudio está representada por el uso del Modelo de Promoción de la Salud, para explicar la utilización adecuada de los servicios de control prenatal; haciendo un análisis de las percepciones sobre los beneficios, barreras y necesidades que manifiesta la gestante; a la vez que informa sobre que estos aspectos tienen con el compromiso de la mujer con el cuidado y provee de información útil a los profesionales de enfermería encargados de organizar, coordinar y realizar estos controles.…”
Section: Discussionunclassified